Hospital Readiness in Several Countries in Dealing with COVID-19 Pandemic: A Systematic Review - Siti Riri Shafira; Anhari Achadi (Health Notions, 2022)
The current COVID-19 pandemic has made the world face the most difficult situation in this decade. Millions of people infected with COVID-19 are of concern to the medical world. The role of the hospital is not spared from this, a place for treatment and infection control. Hospital readiness is very important to respond effectively to this pandemic. The purpose of this systematic review is to find out how far the current hospital readiness in dealing with the COVID-19 pandemic. The analysis was guided by the Rapid Hospital Readiness Checklist developed by WHO to identify preparation and preparedness response to the pandemic that consisted of 12 components i.e leadership, coordination, surveillance, risk communication, patient surge, administration, human resources, primary care, patient management, occupational safety, diagnosis, and infection prevention. The method used was systematic review using PRISMA and search articles through ScienceDirect, Scopus, and Proquest using the keywords "Hospital Readiness and COVID-19". Then the article was analyzed based of the research results of the article on the content. From the selected articles, it is explained that the readiness of hospitals in dealing with the pandemic is still relatively low. The absence of plan development, as well as gaps in human resources, equipment, infrastructure, processes, staff training, and procedures in hospitals, have caused delays in hospital readiness in dealing with the COVID-19 pandemic. requires evaluation and support from the community and government as well as improving the health system in order to increase hospital readiness in dealing with COVID-19 pandemic Keywords: hospital readiness; COVID-19; primary care; WHO checklist